Informal and revolutionary feminist placemaking - Mehan, Asma (Frontiers in Sociology, 2024)
Urban spaces, often emerging outside formal, recognized boundaries, underscore the pivotal role women play in shaping these environments. Despite the enduring influence of patriarchal and hierarchical structures that render these spaces overtly gendered, it is within these contexts that women's actions become particularly transformative. Drawing from feminist urban theories of the global south, this paper investigates informal placemaking, feminist urban activism, revolutionary placemaking, online protest movements, and the networks that support women's solidarity groups. Employing a mixed-methods approach that includes case studies, interviews with activists, and social media analysis, this research focuses on Iran, with a specific emphasis on the recent 'Women, Life, Freedom' movement. This study not only highlights how women navigate, contest, and reshape urban spaces through feminist urban activism and informal revolutionary placemaking but also anticipates the broader implications of these actions for urban planning and policy. By analyzing and comparing these case studies, we aim to uncover the commonalities, differences, challenges, and opportunities between informal/formal, state-led/bottom-up, and revolutionary feminist placemaking practices in Iran. The findings of this paper are expected to contribute valuable insights into the dynamics of feminist urbanism and suggest avenues for future research in enhancing the inclusivity and responsiveness of urban spaces to gendered needs and activism.